A new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from Arunachal Pradesh, India - Poorani, J. (Zootaxa, 2019)
Micraspis unicus sp. nov. (Coleoptera: Coccinellidae) is described and illustrated from the northeastern Indian state of Arunachal Pradesh and compared with other related species. Food preferences in Micraspis are briefly discussed.